Efektivitas Pengelolaan Persediaan dan Peralatan Penanggulangan Bencana di Bidang Logistik pada Badan Penanggulangan Bencana Daerah Kab. Karawang - Faidah, Ananda Dewi Nur; Arnu, Anggi Pasca (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This studi aims to analyze the effectiveness of managing supplies and equipment for disaster management in the logistics sector at the Regional Disaster Management Agency (BPBD) of Karawang Regency. This study was conducted to evaluate the success of BPBD Karawang Regency in managing supplies and equipment used in disaster management efforts. This research also focuses on identifying potential improvements and recommendations to increase the effectiveness of disaster management supplies and equipment management in the logistics sector. The research method used was field surveys, interviews with BPBD officers in Karawang Regency, and analysis of the data obtained. The results of this study are expected to provide a better understanding of the state of management of disaster management supplies and equipment in the logistics sector, as well as provide useful input for BPBD Karawang Regency in improving their performance in this regard. Keywords: Disaster Management, Equipment, Logistics, Supplies, Karawang Regency, Management, Effectiveness, Regional Disaster Management Agency